Recruitment of CCR2+ tumor associated macrophage to sites of liver metastasis confers a poor prognosis in human colorectal cancer. (2nd September 2018) - Grossman, Julie G; Nywening, Timothy M; Belt, Brian A; Panni, Roheena Z; Krasnick, Bradley A; DeNardo, David G; Hawkins, William G; Goedegebuure, S Peter; Linehan, David C; Fields, Ryan C
ABSTRACT: The tumor microenvironment (TME) represents a significant barrier to creating effective therapies for metastatic colorectal cancer (mCRC). In several malignancies, bone marrow derived CCR2 + inflammatory monocytes (IM) are recruited to the TME by neoplastic cells, where they become immunosuppressive tumor associated macrophages (TAM). Here we report that mCRC expression of the chemokine CCL2 facilitates recruitment of CCR2 + IM from the bone marrow to the peripheral blood. Immune monitoring of circulating monocytes in patients with mCRC found this influx was a prognostic biomarker and correlated with worse clinical outcomes. At the metastatic site, mCRC liver tumors were heavily infiltrated by TAM, which displayed a robust ability to dampen endogenous anti-tumor lymphocyte activity. Using a murine model of mCRC that recapitulates these findings from human disease, we show that targeting CCR2 reduces TAM accumulation in liver metastasis and restores anti-tumor immunity. Additional quantitative analysis of hepatic metastatic tumor burden and treatment efficacy found that administration of a small molecule CCR2 inhibitor (CCR2i) improves chemotherapeutic responses and increases overall survival in mice with mCRC liver tumors. Our study suggests that targeting the CCL2/CCR2 chemokine axis decreases TAM at the metastatic site, disrupting the immunosuppressive TME and rendering mCRC susceptible to anti-tumor T-cell responses.